Respuesta :

Answer:

(x, y) = (- 2, 5)

Step-by-step explanation:

given the 2 equations

3y = 11 - 2x → (1)

3x = y - 11 → (2)

Rearrange (2) expressing y in terms of x

add 11 to both sides

y = 3x + 11 → (3)

Substitute y = 3x + 11 into (1)

3(3x + 11) = 11 - 2x

9x + 33 = 11 - 2x ( add 2x to both sides )

11x + 33 = 11 ( subtract 33 from both sides )

11x = - 22 ( divide both sides by 11 )

x = - 2

Substitute x = - 2 in (3) for corresponding value of y

y = (3 × - 2) + 11 = - 6 + 11 = 5

As a check

substitute x = - 2, y = 5 into (1) and (2) and if the left side equals the right side then these values are the solution.

(1) :  left side = (3 × 5) = 15

right side = 11 - (2 × - 2) = 11 + 4 = 15 ⇒ left = right

(2) : left side = (3 × - 2 ) = - 6

right side = 5 - 11 = - 6 ⇒ left = right

solution = (- 2, 5 )



ACCESS MORE